(untitled) (Research, Society and Development, 2021)
In Brazil, one of the most used materials in civil construction is steel, because it has a number of advantages such as: high strength; high ductility; high degree of reliability; smaller and more organized construction site; great ease of reinforcement and expansion; speed of execution. Most steel constructions are horizontal, single-story structures. The sheds make up a large part of this portion, with more versatile and economical solutions that provide large free spans, with a high degree of responsibility, which requires special attention and is essential to be performed by qualified professionals. In view of the demand for qualified professionals and the great growth of the use of steel as a structural system in civil construction, this paper seeks to offer a design guide for the steel structure of a typical shed in the region of Caruaru - PE, which uses cold formed profiles (CFP) in the roof system and hot rolled profiles for the pillars. The SAP2000 software will be used for the modeling and structural analysis of the shed, promoting the appropriate procedure for the structural dimensioning obeying all the pertinent norms, besides doing all the detailing, manufacturing and assembly plans and quantities necessary for the execution of the work. The dimensioning of the structure is pointed out as something complex, being necessary a lot of prudence mainly in the verifications of the connections, because they are largely responsible for the collapse of steel structures, and occur without warning.